Gajah Mada’s Political Legacy: Exploring Leadership Dynamics In Literary Perspectives - Enung Nurhayati; Ramlee bin Tingkong; Suhud Aryana; Muhamad Haryanto; Tato Nuryanto (Jurnal Gramatika, 2024)
This research examines the depiction of Gajah Mada's political framework in literary works, which aims to dissect concepts such as power dynamics, personal interests, policy formulation, and cultural elements, as well as exploring the sharpness of Gajah Mada's leadership.The method used by Alan Swingewood's literary sociology.Data collection and data analysis in this research were carried out by means of literature study, namely first, reading the Gajah Mada novel which was used as the object of study intensively and critically; second, identifying data related to aspects of Gajah Mada's political system; third, inventory or record all identification data.The result of this research is that Gajah Mada's political power, represented as a wise and charismatic leader, highlights Indonesia's need for a democratic, transparent and accountable political system, as well as strengthening national unity and integrity. Gajah Mada's political interests, such as state stability, deconcentration of power, and sustainable development, can be adapted as political alternatives by strengthening checks and balances, independent control institutions, government transparency, community participation, and eradicating corruption. Gajah Mada's political policies succeeded in uniting the archipelago under Majapahit, providing inspiration for Indonesia to improve economic policies, develop justice and eradicate corruption. Gajah Mada's political culture, which involves the mandate of officials, deliberation, and attention to the welfare of the people, can be a basis for strengthening national unity and integrity as well as increasing national awareness through education.